2019
DOI: 10.1021/acs.est.8b05655
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of Wastewater Reuse, Exposure Risk, and Fish Endocrine Disruption in the Shenandoah River Watershed

Abstract: Reuse of municipal and industrial wastewater treatment plant (WWTP) effluent is used to augment freshwater supplies globally. The Shenandoah River Watershed (U.S.A.) was selected to conduct on-site exposure experiments to assess endocrine disrupting characteristics of different source waters. This investigation integrates WWTP wastewater reuse modeling, hydrological and chemical characterization, and in vivo endocrine disruption bioassessment to assess contaminant sources, exposure pathways, and biological eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 73 publications
0
50
0
Order By: Relevance
“…Figure SI.6 shows as a function of distance the degradation of several CECs commonly used as WWTP surrogates (meprobamate, ibuprofen, gemfibrozil, diclofenac, sulfamethoxazole, TCPP and TCEP phosphates) for larger CEC lists that may number in the hundreds of compounds. 5,17,31,34 For a 0.1 m/s streamflow, roughly 50% of the ibuprofen degraded within 100 km, whereas 50% degradation of diclofenac, meprobamate, gemfibrozil, or sulfamethoxazole may not be reached until 300 km. Even longer distances (600 km) may be required for similar degradation of TCPP or TCEP.…”
Section: Proximity Distribution Of Wwtps Upstream To Dwtps Within Thementioning
confidence: 99%
See 2 more Smart Citations
“…Figure SI.6 shows as a function of distance the degradation of several CECs commonly used as WWTP surrogates (meprobamate, ibuprofen, gemfibrozil, diclofenac, sulfamethoxazole, TCPP and TCEP phosphates) for larger CEC lists that may number in the hundreds of compounds. 5,17,31,34 For a 0.1 m/s streamflow, roughly 50% of the ibuprofen degraded within 100 km, whereas 50% degradation of diclofenac, meprobamate, gemfibrozil, or sulfamethoxazole may not be reached until 300 km. Even longer distances (600 km) may be required for similar degradation of TCPP or TCEP.…”
Section: Proximity Distribution Of Wwtps Upstream To Dwtps Within Thementioning
confidence: 99%
“…45 We considered relationships between cancer mortalities and DFR, but as many CECs are pharmaceuticals they do not cause cancer, but rather potentially endocrine disruption or a number of other endpoints that have yet to be epidemiologically supported at low concentrations that occur in drinking waters. 12 One use of this paper could be to locate potential communities for inclusion in such toxicology 17,46 or epidemiology studies.…”
Section: Dwtp Treatment Disparity For Low Population Communities Impamentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impact of de facto reuse on surface water quality and downstream DWTPs is increasingly being studiede.g., for endocrine disrupting compounds and other chemicals of emerging concern Ternes et al 2015;Nguyen et al 2018;Tran et al 2018;Barber et al 2019;Medlock-Kakaley et al 2020), disinfection by-products (DBPs) Weisman et al 2019), and pathogens Amoueyan et al 2017;Caicedo et al 2019;Soller et al 2019). These studies showed a range of wastewater effluent impacts on downstream water quality.…”
Section: Introductionmentioning
confidence: 99%
“…The long-time reuse of low-quality water such as drainage water and wastewater for irrigation could impair soil functions and cause environmental pollution due to salinization, increase of sodium ions relative to other cations, and accumulation of heavy metals (Kabata-Pendias and Mukherjee, 2007;Abegunrin et al, 2016;Balkhair and Mohammad, 2016;Saliba et al, 2018;Cao et al, 2018;Ganjegunte et al, 2018;Abd-Elwahed, 2018 andBarber et al, 2019). There is a number of water quality guidelines related to irrigation according to FAO (Ayers and Westcot, 1985), but none of them is entirely satisfactory because of the wide variability in the environmental conditions, because they concerned about the effect of water quality on soil and crops.…”
Section: Introductionmentioning
confidence: 99%